Therapeutic pipeline for soft-tissue sarcoma - Cassier, Philippe A; Labidi-Galy, Sana Intidhar; Heudel, Pierre; Dutour, Aurélie; Méeus, Pierre; Chelghoum, Maria; Alberti, Laurent; Ray-Coquard, Isabelle; Blay, Jean-Yves (Expert opinion on pharmacotherapy, 2011)
Introduction: Soft-tissue sarcomas (STS) represent a heterogeneous group of malignant tumors originating from connective tissues. Over recent years, this heterogeneity has led to a molecular breakdown of STS and subsequent use of targeted agents in several molecularly defined subgroups. After the initial success of imatinib in gastrointestinal stromal tumors, several other compounds have shown promising activity in some but not all subgroups of sarcoma. Areas covered: This review discusses the rational and clinical results, when available, that support this subtype-directed approach. In the vast majority of cases, these agents have been tested only in patients with advanced disease; as chemotherapeutic agents are developed as non-histotype-specific therapies, they are not discussed here. The PubMed literature was searched using the terms 'sarcoma', 'angiogenesis', 'mTOR' and 'targeted agents'. Proceedings of the annual meeting of the American Society of Clinical Oncology as well as those of the Connective Tissue Oncology Society were also searched for relevant information. Expert opinion: Many agents are currently developed in a subtype-specific manner in STS and this represents a significant leap forward. However, much remains to be done to improve our understanding of the molecular biology of this heterogeneous group of diseases.